2015
DOI: 10.3233/wor-131796
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle and safety practices of firefighters and their relation to cardiovascular risk factors

Abstract: BACKGROUND: In the United States, over 50% of the deaths of on-duty firefighters are classified as sudden cardiac deaths. A holistic view of the multiple risk factors and their relation to the prevalence of cardiovascular disease (CVD) is necessary to determine a baseline for prevention. METHODS: This study surveyed 154 firefighters in a large Midwestern county about their individual exposure to particulates, noise, heat stress, skin contamination, and physical stress; lifestyle factors such as exercise, diet,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 34 publications
1
32
0
2
Order By: Relevance
“…1 These factors lead to an increased risk of cardiovascular disease (CVD), which is the primary cause of on-duty death among firefighters, 2 representing 39% to 50% of on-duty fatalities in US firefighters. [2][3][4] In addition, CVD represents a major cause of morbidity and disability with an estimated 17-25 nonfatal on-duty CVD for every fatal event in this population. 5 On top of classic cardiovascular disease risk factors such as age, smoking, hypertension, obesity, dyslipidemia, diabetes, or preestablished coronary heart disease, firefighters face specific chronic stressors and acute cardiovascular (CV) strains.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 These factors lead to an increased risk of cardiovascular disease (CVD), which is the primary cause of on-duty death among firefighters, 2 representing 39% to 50% of on-duty fatalities in US firefighters. [2][3][4] In addition, CVD represents a major cause of morbidity and disability with an estimated 17-25 nonfatal on-duty CVD for every fatal event in this population. 5 On top of classic cardiovascular disease risk factors such as age, smoking, hypertension, obesity, dyslipidemia, diabetes, or preestablished coronary heart disease, firefighters face specific chronic stressors and acute cardiovascular (CV) strains.…”
Section: Introductionmentioning
confidence: 99%
“…Another study based on focus groups identified 5 main determinants of obesity among firefighters: 1) fire station eating culture, 2) night calls and sleep interruption, 3) supervisor leadership and physical fitness, 4) sedentary work, and 5) age and generational influences. 10 As lifestyle factors are important modifiable predictors of sudden cardiac deaths in firefighters 4 or work ability, 12 a limited number of health promotion interventions have been developed and evaluated among firefighters. The largest intervention implemented is the "Promoting Healthy Lifestyle: Alternative Models'…”
Section: Introductionmentioning
confidence: 99%
“…Despite the extreme physical demands of firefighting, upwards of 80% of firefighters are considered overweight and obese [3], many of whom also express risk factors for cardiovascular disease [22, 23], and do not meet minimum fitness standards [22, 23]. High protein intake has previously been shown to be beneficial for improving body composition and strength [12, 24], yet to date, there has been a lack of quantitative evaluation of protein intake in firefighters.…”
Section: Discussionmentioning
confidence: 99%
“…Many describe food options as limited, expensive, or unhealthy [8]. Some are uneducated about what constitutes a heart healthy diet and others do not recognize themselves as overweight or obese [2]. Ratchford et al [6] found that in firefighters aged 40-58; 86% were overweight or obese, with 46% having an increased waist circumference.…”
Section: Cardiovascular Risk Factorsmentioning
confidence: 99%
“…Many in the public do not realize that of these 70% are volunteer and have other jobs [2,3]. The leading causes of death among firefighters are cardiovascular events, cancer, and motor vehicle accidents [2,4], while sudden cardiac events account for 50% of volunteer and 39% of on duty deaths [2]. Most of the deaths occur during fire suppression [5].…”
Section: Introductionmentioning
confidence: 99%